The Continuity and Change of Pesantren Tradition: Study Network Main Pesantren and Alumni Pesantren in Kabupaten OKU Timur, South Sumatra - Munir (Jurnal Pendidikan Islam, 2016)
This study aims to determine the continuity and change of tradition Pesantren, Study about Network Main Pesantren and Alumni Pesantren in Kabupaten OKU Timur, Sumatera Selatan. This study is a Islamic Educational Sociology research, especially in history of intellectual and Islamic educational institutions in OKU Timur. The approach of continuity and change considers that social phenomena. The result shows that there are three main boarding schools in OKU Timur as a source of tradition pesantren, such as 1). Pesantren Sriwangi. 2). Pesantren Lebak Kajang Lubuk Harjo, Kecamatan Semendawai Suku III, and 3). Pesantren Sukaraja. The three boarding schools are source for the tradition pesantren for more than 20 boarding school alumni in OKU Timur. The source pesantren tradition in OKU Timur, basically based on the same sources of Pesantren tradition, such as the tradition of Javanese pesantren, especially pesantren in East Java.